Progress in the kinetics of slag-metal-gas reactions, past present and future - Coley K.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
From the early days of slag metal reaction studies in the 1950’s to the mid 1980s, a generation of metallurgists contributed much to the theory of slags and their reactions. These workers showed us the importance of charge transfer in slags. They demonstrated that the reaction interface could change dramatically under the influence of reaction and many questions were asked about the specific reaction mechanisms. This paper will review work in slag metal reactions since the mid 1980s and examine our progress in answering some of the questions raised by the early pioneers. The author will focus on recent work from his own laboratory as well as labs from around the World. Finally the author will make some suggestions regarding future directions in this field.